A bright orange luminescence with a single ultra-sharp emission peak in a cubic double perovskite. (December 2022) - He, Zhili; Gao, Meng; Zhuo, Liuyan; Yang, Keqin; Lv, Lifen; Chen, Suqin; Pan, Yuexiao
Abstract: Ba 2+ ions in the cubic double perovskite structure of Ba2 ZnWO6 (BZWO) are coordinated with twelve O ions with high symmetry, and a novel orange phosphor Ba2 ZnWO6 :Eu 3+ (BZWO:Eu) has been obtained by substituting the partial Ba 2+ with Eu 3+ ions by one-step synthesis. The crystal structure and composition, morphology, optical properties, and temperature resistance of the orange phosphor BZWO:Eu have been studied, respectively. Only a single ultra-sharp emission peaking at 596 nm with full width at half maximum (FWHM) of 1 nm has been detected in the emission spectrum of BZWO:Eu, which is originated from the magnetic dipole transition 5 D0 → 7 F1 of Eu 3+ . The photoluminescence (PL) intensity of the phosphor BZWO:Eu has been improved by controlling the experimental condition reaching a PL quantum yield (PLQY) of 53.5%, which is much stronger than that of ZnWO4 :Eu 3+ . The emission peak of BZWO:Eu keeps without any discernable change when the measurement temperature arises from 77 to 300 K, which indicates its superior temperature resistance. Graphical abstract: Only a single ultra-sharp emission peak located at 596 nm with full width at half maximum of 1 nm has been observed in the emission spectrum of Ba2 ZnWO6 :Eu 3+, which is originated from the magnetic dipole transition 5 D0 → 7 F1 of Eu 3+ . Image, graphical abstract